Professional Ethics of Legal Consultants in Handling Copyright Cases in Indonesia - Manuel Mekel (Westscience Press, 2026)
This article examines the professional ethics history: of legal consultants in handling copyright cases in Indonesia. The research employs a normative legal methodology with statute, conceptual, and case approaches. The study analyzes the ethical obligations of legal consultants under the Indonesian Advocate Code of Ethics, Law Number 18 of 2003 concerning Advocates, and Law Number 28 of 2014 concerning Copyright. The findings reveal that the ethical principles of independence, integrity, confidentiality, and conflict of interest management constitute the fundamental pillars governing legal consultants in copyright dispute resolution. The implementation of these ethical standards faces significant challenges due to the complexity of copyright law, the digital transformation of creative industries, and the commercial pressures inherent in legal practice. The article recommends the strengthening of oversight mechanisms, the development of specialized ethical guidelines for intellectual property practitioners, and the establishment of continuous professional education programs to enhance ethical compliance among legal consultants.